2005
DOI: 10.1021/nl050274q
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Self-Assembly of Spherical Oligomers

Abstract: In multistep reactions, stability of intermediates is critical to the rate of product formation and a significant factor in generating kinetic traps. The capsid protein of cowpea chlorotic mottle virus (CCMV) can be induced to assemble into spherical particles of 30, 60, and 90 dimers. Based on examining assembly kinetics and reaction end points, we find that formation of uniform, ordered structures is not always a result of reactions that reach equilibrium. Equilibration or, alternatively, kinetic trapping ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
145
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(163 citation statements)
references
References 25 publications
18
145
0
Order By: Relevance
“…Following the early work of Fraenkel-Conrat and Williams [10], it was found that many small RNA viruses can assemble spontaneously under in-vitro conditions in solutions containing the capsid proteins and the RNA genome molecules. The self-assembly of empty capsids has been shown to have the character of a first-order, activated process [11]. This is consistent with the nucleation-and-growth of "proteinby-protein" assembly models [12] where capsid proteins diffuse in towards partially assembled protein shells.…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…Following the early work of Fraenkel-Conrat and Williams [10], it was found that many small RNA viruses can assemble spontaneously under in-vitro conditions in solutions containing the capsid proteins and the RNA genome molecules. The self-assembly of empty capsids has been shown to have the character of a first-order, activated process [11]. This is consistent with the nucleation-and-growth of "proteinby-protein" assembly models [12] where capsid proteins diffuse in towards partially assembled protein shells.…”
Section: Introductionsupporting
confidence: 71%
“…An interesting extension of the theory would be to study its kinetics and the relation to the current nucleation-and-growth description of capsid assembly [11,46]. Based on numerical simulations [47], it is expected that when the binding affinity between different capsid proteins increases with respect to the binding affinity between capsid proteins and RNA then nucleation and growth will start to dominate over the collective scenario that is the focus of this paper.…”
Section: Hk97mentioning
confidence: 99%
See 1 more Smart Citation
“…In this discussion we assume that cores are commensurate with the size and geometry of capsids; we discuss the general case elsewhere. If there is no assembly of adsorbed subunits, the equilibrium surface concentration of subunits can be calculated for Langmuir adsorption (8) where β = 1/k B T is the inverse of the thermal energy, and g c is the surface-subunit free energy. The adsorption timescale is τ ad = n s /k ad C S , with k ad the adsorption rate constant, and the number of adsorbed subunits at saturation, n s = N σ 3 c surf .…”
Section: A the Kinetics Of Core-controlled Assemblymentioning
confidence: 99%
“…[7][8][9][10][11][12] Multiscale analysis is a natural way to understand these phenomena. [13][14][15] In the present approach, OPs are used to capture the slow overall transformation of a system from one state to another.…”
Section: Introductionmentioning
confidence: 99%